New Heterocyclic Organosulfur Compounds Derived from Dithioacetals - Leja, Dawid T.; Depa, Wojciech J.; Guńka, Piotr A.; Zachara, Janusz; Lechowicz, Jaromir B.; Groszek, Grazyna (Synlett, 2024)
The dithioacetalization of lactaldehyde derivatives with ethane-1,2-, propane-1,3-, butane-1,4-, and pentane-1,5-dithiols in the presence of 4 mol% of scandium triflate has been described. A series of cyclic dithioacetals were obtained with yields ranging from quantitative to 37%. The dithioacetalization of lactaldehyde derivatives with butane-1,4-dithiol and pentane-1,5-dithiol groups are accompanied by the formation of 14- and 16-membered macrocyclic sulfur structures with yields of 3% and 18%, respectively. In the case of a cyclic dithioacetal derivative with three methylene groups, a diastereoisomeric pair of enantiomers was obtained, the structure of which was confirmed by single-crystal X-ray diffraction analysis. Dithioacetals are useful building blocks in the synthesis of complex chemical structures. Macrocyclic compounds can be used to complex metal ions.
Keywords: lactic aldehyde; chiral cyclic dithioacetals; scandium triflate; sulfur macrocycle; dithioacetalization